An Analysis of Land Use Options in Kitengela and its Effect on Conservation and Management of Nairobi National Park - Odwori , Paul Okelo; Ipara , Hellen; Obare , Dermmillah Fridah (African Journal of Education,Science and Technology (AJEST), 2014)
Nairobi National Park is unable to incorporate the spatial and temporal dynamics of many migratory mammals that rely on the area as a dry season refuge because of its small size. This has been made even worse by human encroachment on the park area. During the wet season, wild animals must be able to migrate to the south into the Kitengela dispersal area. However, Kitengela is under private ownership and currently in a process of subdivision, fencing, and conversion of grasslands to croplands and settlements thus jeopardizing its capacity to contribute to the dispersion of wildlife and hence the viability of the park. This study analyzed land-use options in the Kitengela area and their effect on Nairobi National Park. Data was collected using questionnaires, interviews, discussions and observations. Data was analyzed using descriptive statistics, cross tabulations and chi-square (χ2) test with the help of the Statistical Package for Social Scientists (SPSS). All data were tested at the 95% (0.05) level of significance. Results indicate that although wildlife conservation would give the highest income of a monthly average of Kshs 27,500, the Kitengela land-owners preferred to put their land under residential houses and commercial buildings which would give them an average monthly income of Kshs 24,286. The study recommends that policy should be formulated to regulate utilization of land in Kitengela area in order to create room to facilitate the dispersion of wild animals to and from Nairobi National Park.